On the Economic Growth Effect of Population: Evidence from World Most and Least Populous Countries - Olubiyi, Ebenezer Adesoji; Olaifa, Felix Gbenga; Amusan, Boluwatife (Acta Universitatis Danubius. Œconomica, 2023)
This study assesses the importance of population growth in economic growth in the six most populous and six least populous countries in the world for data spanning 1985 to 2022. Results from the panel autoregressive distributed lag indicate that population has no significant effect on economic growth in the short run in any of the country groups but it shows positive relationship. Population enhances economic growth more in the most populous countries than in the least populous countries in the long run. In addition, population is persistent in impacting economic growth of the most populous countries. Decrease in unemployment rate enhances economic growth rate more in the least populous countries than in the most populous countries. Human capital development is also important for economic growth and more pronounced in the least populous countries. Following these results, it is concluded that population matters importantly for economic growth and that the most populous country is more likely to experience higher economic growth than the least populous country. The study recommends that that a carefully planned population growth strategy will be beneficial to both country groups. In the most populous countries, plans that will allow for more inflow of peoples should be looked forward into because most of these countries are embarking on birth control in order to reduce population. It is also recommended that the least populous countries should ensure that a considerable size of the population translates to human capital